2019
DOI: 10.1109/access.2019.2925861
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Nonlinear Oscillations in Process Control Loop Based on an Improved VMD

Abstract: A novel detector based on improved variational mode decomposition (VMD) is proposed to detect the nonlinearity-induced oscillations. Despite its high adaptivity and frequency resolution, the effectiveness of VMD highly depends on parameters, including mode number K , initial center frequency ω init , and the penalty coefficient α. To tackle this problem, an improved VMD is proposed, which involves: 1) the spectrum of phase-rectified signal averaging (PRSA) to determine optimal K , ω init and 2) the summation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In the end, the SISO experiments and various industrial cases demonstrate the utility and advantages of the proposed oscillation detection and characterization framework. Compared with the the existing detection techniques based on EMD [13] and VMD [22], the proposed method is more accurate and reliable. Therefore, it can be concluded that this study has great potential values for control performance monitoring.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the end, the SISO experiments and various industrial cases demonstrate the utility and advantages of the proposed oscillation detection and characterization framework. Compared with the the existing detection techniques based on EMD [13] and VMD [22], the proposed method is more accurate and reliable. Therefore, it can be concluded that this study has great potential values for control performance monitoring.…”
Section: Discussionmentioning
confidence: 97%
“…The detection and characterization results listed in Table 2 are well consistent with the prior knowledge, which demonstrates the effectiveness of the proposed method. In order to highlight the advantages of the proposed [13] and VMD-based [22] methods are used to detect the oscillations contained in these data. The decomposition plots for the three misclassified cases using EMD (for pulp and papers, metals), or VMD (for mining) are provided in Figure 20, 21, and 22, respectively.…”
Section: Industrial Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillations are one of the most common problems in process control systems [1]. Oscillation behavior will seriously affect the control system performance, such as reducing the product quality and uniformity, increasing the energy consumption, wasting the raw materials and even causing the plant down [2]. It is reported that over 30% control loops are oscillating because of the presence of nonlinearity problems [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…These methods firstly decompose the multi-component acceleration signals into single-component intrinsic mode functions (IMFs) using the mode decomposition method, and then, identify the instantaneous frequency of the IMFs using time-frequency analysis method. Among all the mode decomposition methods, variational mode decomposition (VMD) [38] is gradually well-known because it can overcome the shortcomings of modal aliasing [39], [40]; Among all the time-frequency analysis method, synchrosqueezed wavelet transform (SWT) [41] is widely used because it can obtain time-frequency distribution curves with high frequency accuracy [42], [43].…”
Section: Introductionmentioning
confidence: 99%